Incidence of Rotavirus Diarrhea in Children Admitted to Nakornping Hospital - Niraroot, Wirat; Chutipongwiwet, Salakchit; Tanakehas, Chanpen (Journal of Health Science of Thailand, 1994)
143 children under 5 years of age who were admitted to Nakomping Hospital over a twelve month period from June 1993 to May 1994 for diarrhea were included in this study. They were clinically evaluated, their histories taken and collected stool for examination by PAGE method. It was found that the incidence of rotavirus diarrhea was 31.5 percent. In this study the clinical features of rotavirus diarrhea included watery diarrhea, fever and vomiting, and the highest incidence was in children under 2 years of age as well as the peak seasonal distribution was in winter. There was no statistically signiﬁcant difference of rotavirus infection between the children dwelling in the better santitary area, as some city or town, and the ones dwelling in the rural area. During the efﬁcacious rotavirus vaccine have not succeeded producting yet, the alternative measure to reduce the incidence of rotavirus infection in children would be convincing and supporting mothers the family health.